The role of lipid peroxidation in the pathogenesis of experimental diabetic retinopathy - Y. Sirman; I. Savytskyi (Kazimierz Wielki University, 2021)
The aim of work - to analysis of changes in the level of primary products of lipid peroxidation in experimental animals were simulated diabetic retinopathy and against the background of its correction. The obtained results indicate an increase in the content of lipid peroxidation, starting from the 30th and with further progression on the 60th and 180th days of experimental diabetic retinopathy, which is confirmed by an increase in the level of diene conjugates in the 2nd group, the maximum of which is observed at the 3rd stage. Correction with hypoglycemic agents in the 3rd group had a positive effect, but was not able to reduce the level of primary products of lipid peroxidation and restore antioxidant activity, so the use of additional agents became necessary. The use of aflibercept and a nitric oxide donor in the 4th group to correct the development of diabetic retinopathy significantly suppressed oxidative stress, the maximum of which occurred on the 180th day of the experiment, but did not reach control indicators. It was proven that the combined administration of bromfenac and aflibercept in the 5th group significantly reduced the number of primary LPO products, but not as significantly as in the 4th group. It was proved that the administration of aflibercept, L-carnitine and bromfenac to the animals of the 6th group reduced the content of diene conjugates already on the 30th and continued on the 60th and 180th days of the study, but it also did not reach the control indicators. The combination of metformin, aflibercept, L-arginine and citicoline in rats of the 7th group proved to be the most effective correction, as evidenced by the normalization of the level of the studied indicators on the 30th and 60th days of the experiment, and on the 180th, a decrease in the content of markers was detected oxidative stress to control indicators.